Simultaneous Determination of Bergapten, Imperatorin, Notopterol, and Isoimperatorin in Rat Plasma by High Performance Liquid Chromatography with Fluorescence Detection and Its Application to Pharmacokinetic and Excretion Study after Oral Administration of Notopterygium incisum Extract. (26th December 2016) - Teye Azietaku, John; Yu, Xie-an; Li, Jin; Hao, Jia; Cao, Jun; An, Mingrui; Tan, Zhijing; Chang, Yan-xu
Abstract : A specific, sensitive, and reliable high performance liquid chromatography with fluorescence detection (HPLC-FLD) was first optimized and then used in the simultaneous quantification of bergapten, imperatorin, notopterol, and isoimperatorin in rat plasma using osthole as the internal standard. Liquid-liquid extraction with ethyl acetate was employed in treating the rat plasma samples obtained. Separation was carried out with a Hedera™ ODS column (4.6 × 250 mm, 5  μ m) by gradient elution at a temperature of 40°C. Excitation and emission of the fluorescence detector were set to 300 and 490 nm, respectively. The lower limits of quantification for bergapten, imperatorin, notopterol, and isoimperatorin in rat plasma were 4, 40, 4, and 2 ng mL −1, respectively. The intraday and interday precision and accuracy for the four coumarins were within acceptable criteria. The recovery of the method was satisfactory with a range of 80.3–114%. The validated method was successfully used for the simultaneous determination of the four coumarins in Notopterygium incisum extracts and also for the pharmacokinetic and excretion study of bergapten, imperatorin, notopterol, and isoimperatorin in rats.